Herpetofauna diversity in Sg. Deka, Hulu Terengganu, Peninsular Malaysia / Nur Amalina Mohd Izam - Mohd Izam, Nur Amalina; Ahmad, Norhayati; Md. Nor, Shukor; Nazron, Nur Syuhada; Muhammad Nazir, Nurul Adyla; Magintan, David; Farinordin, Farah Ayuni; Amat Darbis, Nurul Darsani; Zainul Abidin, Mohamad Kamaruddin (Universiti Teknologi MARA Cawangan Pahang, 2021)
Sg. Deka is located in Tembat Forest Reserve (TFR), the largest forest reserve in Terengganu. Sg. Deka is known to have ecological bridges for wildlife crossings and serves as a corridor for wildlife to the national park. Sg. Deka is a protected area that serves as a wildlife release site and houses many species of fauna. This survey was conducted in Sg. Deka with the aim of determining the herpetofaunal diversity. The survey was conducted from August 2014 to July 2015. Fenced-pitfall traps and visual encounter survey method were used, as combination of various methods increases the chance to find more species in an area. A species diversity checklist of the herpetofauna in Sg. Deka is presented. A total of 119 herpetofauna individuals were found, comprising of 75 amphibians and 44 reptiles. This checklist includes 12 amphibian species from five families, namely Bufonidae, Dicroglossidae, Megophryidae, Microhylidae, and Ranidae; and 14 reptile species from four families, namely Agamidae, Gekkonidae, Scincidae, and Colubridae. The most dominant species found was Ingerophrynus parvus. Further surveys need to be carried out to discover more herpetofauna in Sg. Deka area.